Kesan Paras N dan K dalam Larutan Nutrien terhadap Keupayaan Pertukaran Kation Akar Tanaman Selada (Lactuca sativa) - A. Kazar, Mazuki; Hussin, Aminuddin; Abdul Raffar, Khalip (Universiti Putra Malaysia Press, 1994)
A study on the influence of nitrogen (N) (100, 200, 300 and 400 mgNL-l ) and potassium (K) (100, 200 and 400 mgKL-l) combinations in solution using the nutrient film technique, hydroponic system on the root cation exchange capacity (GE.G) of lettuce plant (Lactuca sativa var crispa cv. Poly) was undertaken. Roots were sampled on the 20th, 30th and 40th day after germination. Significant increase in roots GE. Cfrom 39.4 7 to 51.11 cmol(+)kgl due to the N level was only detected on the 40th day of sampling. However, increasing the k concentration in nutrient solution at the three sampling times significantly decreased the root GE.C values from 29.48-57.00 to 23.25-35.92 cmol(+)kgl . Root GE.C increased from 27.1 7 to 46.23 cmol(+)kg1 with plant growth stage.